Perencanaan Dan Perancangan Wellness Center Dengan Pendekatan Healing Environment Di Desa Angseri, Baturiti, Tabanan, Bali - Michael Cartens Bahy Bahy; Ni Wayan Meidayanti Mustika; I Ketut Sugihantara (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
The island of Bali is one of the main tourist spa destinations in the central part of Indonesia and is also one of the best tourist destinations in the world. The response to the development of tourism shown by the government with the creation of the Fitness Travel Book